β-Hydroxybutyrate Attenuates Painful Diabetic Neuropathy via Restoration of the Aquaporin-4 Polarity in the Spinal Glymphatic System - Wang, Fei-xiang; Xu, Chi-liang; Su, Can; Li, Jiang; Lin, Jing-yan (Frontiers in Neuroscience, 2022)
Waste removal is essential for maintaining homeostasis and the normal function of the central nervous system (CNS). The glymphatic system based on aquaporin-4 (AQP4) water channels on the endfeet of astrocytes is recently discovered as the excretion pathway for metabolic waste products of CNS. In the CNS, α-syntrophin (SNTA1) directly or indirectly anchors AQP4 in astrocyte membranes facing blood vessels. Studies have indicated that β-Hydroxybutyrate (BHB) can raise the expression of SNTA1 and thus restore AQP4 polarity in mice model with Alzheimer's disease. The study aims to evaluate the neuroprotective mechanism of BHB in rats with painful diabetic neuropathy (PDN). PDN rats were modeled under a high-fat and high-glucose diet with a low dose of streptozotocin. MRI was applied to observe the clearance of contrast to indicate the functional variability of the spinal glymphatic system. Mechanical allodynia was assessed by paw withdrawal threshold. The expressions of SNTA1 and AQP4 were tested and the polarity reversal of AQP4 protein was measured. As demonstrated, PDN rats were manifested with deceased contrast clearance of the spinal glymphatic system, enhanced mechanical allodynia, decreased expression of SNTA1, increased expression of AQP4, and reversed polarity of AQP4 protein. An opposite change of the above characteristics was observed in rats being treated with BHB. This is the first study that demonstrated the neuroprotective mechanism of BHB to attenuate painful diabetic neuropathy via restoration of the AQP4 polarity in the spinal glymphatic system and provides a promising therapeutic strategy for PDN.